Unification of Physics Theories by the Ether Elasticity Theory (Global Journal of Science Frontier Research, 2014)
Abstract not found
Keywords: ether theory as unifying; moving particle as a globule in the ether; newton approximation; orentz transformation of static potential; globule motion c